Indonesian History Educational Card Game Gamification of the Process of Learning to Increase Interest in History among Children. - Wildan Ali; Vera Jenny Basiroen; Clara Fang (Bina Nusantara University, 2018)
To spark interest and curiosity in children to make them research more about the subject. The writers also aims to re-tell history in a more visual manner which is more attractive to children as oppose to currently used text heavy history book and to make history more interesting by using an interactive teaching method by using gamification.